Atomic force microscopy probing interactions and microstructures of ionic liquids at solid surfaces. Issue 31 (25th July 2022) - An, Rong; Laaksonen, Aatto; Wu, Muqiu; Zhu, Yudan; Shah, Faiz Ullah; Lu, Xiaohua; Ji, Xiaoyan
Abstract : This review showcases the recent progress of atomic force microscopy in clarifying the interactions of ionic liquids with solid interfaces at the nanoscale to understand the microstructure and mechanisms. Abstract : Ionic liquids (ILs) are room temperature molten salts that possess preeminent physicochemical properties and have shown great potential in many applications. However, the use of ILs in surface-dependent processes, e.g. energy storage, is hindered by the lack of a systematic understanding of the IL interfacial microstructure. ILs on the solid surface display rich ordering, arising from coulombic, van der Waals, solvophobic interactions, etc., all giving near-surface ILs distinct microstructures. Therefore, it is highly important to clarify the interactions of ILs with solid surfaces at the nanoscale to understand the microstructure and mechanism, providing quantitative structure–property relationships. Atomic force microscopy (AFM) opens a surface-sensitive way to probe the interaction force of ILs with solid surfaces in the layers from sub-nanometers to micrometers. Herein, this review showcases the recent progress of AFM in probing interactions and microstructures of ILs at solid interfaces, and the influence of IL characteristics, surface properties and external stimuli is thereafter discussed. Finally, a summary and perspectives are established, in which, the necessities of the quantification of IL–solid interactions at the molecular level, the development of in situ techniques closely coupled with AFM for probing IL–solid interfaces, and the combination of experiments and simulations are argued.